Caring Personality Traits Among Indonesian Nursing Students and Clinical Nurses: A Cross-Sectional Study - Kuntarti Kuntarti; Yeni Rustina; Jahja Umar; Dewi Irawaty (PT.Mantaya Idea Batara, 2026)
Background: Caring is fundamental to professional nursing practice and identity. However, limited research has examined the caring personality trait among Indonesian nursing students and nurses. Methods: This cross-sectional study examined these traits and analyzed subgroup differences among nursing professional students and clinical nurses using the Inventori Kepribadian untuk Ners–Praktis (IKUN-P). The IKUN-P demonstrated strong internal consistency (Cronbach’s alpha 0.824–0.902). Data were collected from 488 participants across three Indonesian regions through convenience sampling. Results: The majority of participants were female (72.75%) and 25 years old or younger (46.31%). Among the five traits assessed, optimism had the highest mean score (33.29 ± 4.75), reflecting a generally positive outlook. Emotional intelligence the lowest mean score (30.48 ± 4.83), indicating a potential area for educational and professional development. Analysis identified significant regional differences in emotional intelligence (p=0.046), optimism (p=0.043), emotional stability (p=0.007), and personal integrity (p=0.004). Most traits did not differ by age, gender, education, work experience, or respondent type (p>0.05). Limitations of the study include its cross-sectional design, self-report measures, and convenience sampling. Conclusion: The results indicate that programs promoting emotional intelligence and optimism could support caring behavior and professional performance among nursing students and nurses.